Application of the Project Based Learning Model in Improving Student Discipline in PAI Subjects at SMP Islam Insan Kamil An-Nahdliyah - Zalsanudin, Virgie Ramadhani; Masnawati, Eli (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2024)
This study examines the implementation of the Project-Based Learning (PjBL) model in learning Islamic Religious Education (PAI) and its contribution to the formation of student discipline. Using a descriptive qualitative approach, this study was conducted at Insan Kamil An-Nahdliyah Islamic Junior High School, a pesantren-based school in Sidoarjo, Indonesia. Data collection techniques included participatory observation in the classroom, in-depth interviews with PAI teachers, students, and the school principal, as well as analysis of learning documents such as lesson plans and student project results. Thematic analysis was used to identify patterns of student engagement, changes in discipline behavior, and contextual factors that influence the effectiveness of the PjBL model. The results showed that PjBL not only increased cognitive engagement, but also supported the development of affective and psychomotor aspects simultaneously. The model encourages collaboration, reflection, time management and learning independence - important indicators of disciplined and organized learning. Furthermore, PjBL provides a pedagogical space for the internalization of Islamic values in a contextualized manner, especially when projects are designed in line with Islamic moral and social principles. The teacher's role as a facilitator and the integration of character values in the project activities proved crucial in shaping a disciplined and responsible learning environment. This study confirms the importance of integration between innovative learning models and value-based education in improving the quality of PAI learning. The findings open up opportunities for further exploration in different educational contexts, including quantitative studies related to the character impact of the project-based approach